STUDENTS' METACOGNITIVE SKILLS AND CRITICAL READING SKILLS OF KOREAN TEXTS: HOW DO THEY CORRELATE? - Ansas, Velayeti Nurfitriana; Azizah, Asma; Oktavianto, Dwi Bhakti; Nasihin, Siti Balqis (International Journal of Education, 2023)
Metacognitive skills are considered a pivotal modal for students to develop critical literacy, especially in reading activities, as part of the main goals of 21st-century language education. These skills also help the students succeed in their learning process because they involve the ability to evaluate one's capacity and achievement in learning. Although much research has been initiated, Korean as a foreign language (KFL) student is little known. To fill the void, this ongoing study investigates the level of metacognitive skills in reading among Indonesian undergraduate students majoring in Korean language education. Employing a descriptive quantitative approach, the researchers distributed a questionnaire and interview on students’ metacognitive skills in critical reading.  What about items about critical reading skills? It also turned out you have interview data. please include here in the abstract. The data were analyzed, focusing on the mean scores and percentages to get the main points of the student's responses and how students apply their metacognitive skills in critical reading. The results showed that as many as 75% of students had a moderate level of metacognitive skills, and only 5.5% had a high level of metacognitive skills. This shows that students' metacognitive abilities still need to be improved.  Of the eight indicators measured, the ability in time management shows a low value. Meanwhile, the ability to implement strategies shows a high value. It can be concluded that students still have to improve their metacognitive skills in critical reading, especially in time management.